Government Strategic Policy in Agricultural Development - Supendi Supendi (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
It is very important to implement agricultural sector policies in Indonesia. The Agricultural Census conducted by the Central Statistics Agency provides agricultural data needs both at the national and global levels. The policy in the 2023 Agricultural Census (ST2023) activities is designed so that the results obtained are of international standard. The International Standard Agricultural Census refers to the FAO program known as the World Program for the Census of Agriculture (WCA). With the realization of Food Security starting from the individual and household levels, villages, sub-districts, districts, provinces to National Food Security becomes a national goal. Through food security policies, one of the important elements of national security can be implemented. Therefore, the government intensively cooperates to realize Food Security and Farmer Welfare. Food security targets in 2024 self-sufficiency in industrial sugar and 2026 self-sufficiency in beef, towards Indonesia's Vision in 2045 to become a World Food Barn. The food policy achievements above have also improved the welfare of farmers. This can be seen from the poverty indicator in rural areas in March 2021 at 13.10 percent, down to 12.53 percent in September 2021. (BPS, 2021). In guarding and ensuring that the structural transformation process can be carried out in a precise and directed manner, various policies that have been and will be implemented need to be supported by an accurate agricultural database. Then strengthen infrastructure, financial institutions, farmer's markets and others. Capacity building of Human Resources (HR) to become professional and productive. The key actor in agricultural development policy is to utilize the results of the agricultural census. A strategic and sustainable agricultural data ecosystem. Then the availability and accessibility of data and awareness of data users that the data exists. The government needs to make policies that are pro-Agricultural sector right on target.